Observations on the age and growth of Varicorhinus damascinus (Val.) in Tigris river at Salahuldin province – Iraq - Baghdad Science Journal (مجلة بغداد للعلوم, 2008)
Age and growth of Varicorhinus damascinus (Val.) in Tigris river at Salahuldin province have been investigated. Monthly samples were taken during the period from September 1999 to August 2000, using small-meshed gill nets. The age data showed that there were six age groups and the dominant age groups were (III – IV) for both sexes. The results of the present study revealed that the increment in length of V. damascinus at the sites of study showed a tendency to decrease with the increase in age, after the third year of life in both sexes. The length-weight relationship of males and females were calculated and demonstrated in a straight line logarithmic formula, as follows: Log W = 1.5404 + 2.6885 log L for males r = 0.95 (P > 0.05) Log W = 1.6723 + 2.7877 log L for females r = 0.77 (P > 0.05) The values of the regression coefficient (b) indicated that the growth of both sexes of V. damascinus was allometric..